Global Assemblages and National Narratives - Saija Volmari (Nordic Journal of Comparative and International Education)
This article builds on the author’s doctoral dissertation and the accompanying lectio praecursoria, offering a critical reflection on evidence-based policymaking in Nordic school reforms. Drawing on assemblage thinking and spatiotemporal theory, it explores how global policy discourses and national ambitions are interwoven through networks of experts and knowledge. The article highlights the contested and co-constructed nature of evidence-based policymaking, shaped by multiple actors and sites in national, Nordic and global policy spheres. It argues for a nuanced and relational understanding of policy space—one that enables researchers to trace sites and situations of policymaking and identify potential moments of interruption. These ideas are further developed in the author’s current postdoctoral project, which follows future vision for comprehensive education in the making in Finland.